RARE EARTH ELEMENT GEOCHEMISTRY AND PETROGENESIS OF MILES (IIE) SILICATE INCLUSIONS - Hsu W. (My University, 2003)
An ion probe study of rare earth element (REE) geochemistry of silicate inclusions in the Miles IIE iron meteorite was carried out. Individual mineral phases among inclusions have distinct REE patterns and abundances. Most silicate grains have homogeneous REE abundances but show considerable intergrain variations between inclusions. A few pyroxene grains display normal igneous REE zoning. Phosphates (whitlockite and apatite) are highly enriched in REEs (50 to 2000 x CI) with a relatively light rare earth element (LREE)-enriched REE pattern. They usually occurred near the interfaces between inclusions and Fe host. In Miles, albitic glasses exhibit two distinctive REE patterns: a highly fractionated LREE-enriched (CI normalized La/Sm ~15) pattern with a large positive Eu anomaly and a relatively heavy rare earth element (HREE)-enriched pattern (CI-normalized Lu/Gd ~4) with a positive Eu anomaly and a negative Yb anomaly. The glass is generally depleted in REEs relative to CI chondrites.The bulk REE abundances for each inclusion, calculated from modal abundances, vary widely, from relatively depleted in REEs (0.1 to 3 x CI) with a fractionated HREE-enriched pattern to highly enriched in REEs (10 to 100 x CI) with a relatively LREE-enriched pattern. The estimated whole rock REE abundances for Miles are at ~ 10 x CI with a relatively LREE-enriched pattern. This implies that Miles silicates could represent the product of a low degree (~10%) partial melting of a chondritic source. Phenocrysts of pyroxene in pyroxene-glassy inclusions were not in equilibrium with coexisting albitic glass and they could have crystallized from a parental melt with REEs of ~ 10 x CI. Albitic glass appears to have formed by remelting of preexisting feldspar + pyroxene + tridymite assemblage. Yb anomaly played an important role in differentiation processes of Miles silicate inclusions; however, its origin remains unsolved.The REE data from this study suggest that Miles, like Colomera and Weekeroo Station, formed when a molten Fe ball collided on a differentiated silicate regolith near the surface of an asteroid. Silicate fragments were mixed with molten Fe by the impact. Heat from molten Fe caused localized melting of feldspar + pyroxene + tridymite assemblage. The inclusions remained isolated from one another during subsequent rapid cooling.